Transtracheal lidocaine: An alternative to intraoperative propofol infusion when muscle relaxants are not used - Sunil Rajan; Nitu Puthenveettil; Jerry Paul (Wolters Kluwer Medknow Publications, 2014)
Background: Facial nerve monitoring, often required during total parotidectomy, precludes use of long acting muscle relaxants and propofol infusion is used solely to ensure patient immobility. We aimed to compare intraoperative patient immobility, hemodynamic stability and propofol consumption during total parotidectomy following a transtracheal block. Material and Methods: Forty patients were allocated to 2 equal groups. Preoperatively, group A patients received transtracheal block with 4 ml of 4% lidocaine, while no block was given to patients in group B. If there was patient movement, tachycardia or hypertension, group A patients received a bolus of propofol 30 mg and propofol infusion was started (100mg/hr). In group B, propofol infusion was started (100mg/hr) soon after intubation. Result: Both group A and B were comparable with respect to patient immobility and hemodynamic stability. There was no intraoperative propofol requirement in group A. Conclusion: Transtracheal block is a safe and successful alternative to propofol infusion during surgeries where muscle relaxants are to be avoided.